Mapping design-driven processes for the regeneration of small fortified towns in inland areas - Massimo Brignoni; Giorgio Dall’Osso; Silvia Gasparotto; Riccardo Varini (Agathón)
The contribution aims to focus on and deal with a methodology of mapping, typifying and cataloguing selected design interventions based on the impacts that the various design disciplines are or have been able to induce at different scales of action in the contexts of small fortified towns, constituting the primary settlement cores of the so-called inland areas. The main keys of research, filing and reading chosen for mapping allow the infographic schematisation of study in a Cartesian diagram based on two primary axes. The taxonomy, developed and adopted by the Design Research Unit of the University of San Marino, identifies, distributes and classifies numerous case studies according to two essential relational variables between human beings, communities and places: the time of permanence and the level of interaction and involvement with the areas.